The zoo box - Cohn, Ariel (First Second, 2014)
"When Erika and Patrick's parents leave them home alone for the night, they head straight to the attic to explore. When they open a mysterious box, hundreds of animals come pouring out! Soon the town is awash in more and more zoo animals, until Erika and Patrick discover that the tables have been turned... and the animals now run a zoo full of humans!" --